4TEFFECTS OF GRAIN SIZE, ROUGHNESS, AND HARDNESS OF SEA FLOOR ON BACK SCATTERING VALUE BASED ON HYDROACOUSTIC DETECTION - Sri Pujiyati; Sri Hartati; Wijo Priyono (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
3TBased on results of detection hydroacoustic, backscattering value from the first reflection (E-1) can describe the roughness and from the second reflections (E-2) can describe the hardness of sea floor. The objective of this study was to analyze the relationship between grain size, roughness and hardness with backscattering values using the hydroacoustic method. The results showed that the roughness, hardness, and diameter size fraction of fine sand substrate were greater than that of muddy sand substrate. The backscattering values of very fine sand substrate were also greater than that of muddy sand substrate.Keywords: Hydroacoustic, bottom, backscattering